Global multidimensional poverty and COVID-19: A decade of progress at risk? - Alkire, S; Quinn, NN; Nogales, R; Suppa, N (Oxford Poverty and Human Development Initiative, 2021)
According to the global Multidimensional Poverty Index (MPI), an internationally comparable measure, poverty in developing countries has fallen substantially over the last 15 years. The COVID-19 pandemic and associated economic contraction are negatively impacting multiple dimensions of poverty and jeopardising this progress. This paper uses quantitative assessments of increases in food insecurity and out of school children made by UN agencies to inform microsimulations of potential impacts of the pandemic under six alternative scenarios. These simulations use the nationally representative datasets underlying the 2020 update of the global MPI. Because these datasets were collected between one and 12 years pre-pandemic, we develop models to translate the simulated impacts to 2020 while accounting for underlying poverty reduction trends and country-specific factors. Aggregating results across 70 countries that account for 89% of the global poor according to the 2020 global MPI, we find that the potential setback to multidimensional poverty reduction is between 3.6 and 9.9 years under the alternative scenarios.